2019
DOI: 10.1017/sjp.2019.46
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying, Self-concept and Academic Goals in Childhood

Abstract: Cyberbullying has aroused scientific interest given the impact it has on the lives of young people. The present study proposes to analyze the relationship between self-concept (Self-Description Questionnaire I), academic goals (Achievement Goals Tendencies Questionnaire), and the participation of the roles of victim, bully and bystander in cyberbullying (Cyberbullying. Screening for peer bullying and cyberbullying), by gender and grade. The sample was composed of 548 students (49.8% girls) in 5th and 6th grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
5
12
1
Order By: Relevance
“…This evidence is congruent with the results of Jenkins and Kilpatrick [ 30 ] and Blakely-McClure and Ostrov [ 31 ], who used path analyses to indicate that self-concept and cybervictimization are negatively associated. This is consistent with studies that have also found this relationship in the specific dimensions of self-concept, such as academic self-concept [ 26 ], self-concept referring to relationships with parents and peers [ 29 ], and general self-concept [ 26 , 27 , 29 ]. Therefore, negative self-perceptions during preadolescence may be risk factors for becoming a cybervictim.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This evidence is congruent with the results of Jenkins and Kilpatrick [ 30 ] and Blakely-McClure and Ostrov [ 31 ], who used path analyses to indicate that self-concept and cybervictimization are negatively associated. This is consistent with studies that have also found this relationship in the specific dimensions of self-concept, such as academic self-concept [ 26 ], self-concept referring to relationships with parents and peers [ 29 ], and general self-concept [ 26 , 27 , 29 ]. Therefore, negative self-perceptions during preadolescence may be risk factors for becoming a cybervictim.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it is found that adolescents having higher levels of school anxiety are less likely to positively perceive their social relations with their peers or parents, in addition to perceiving themselves as being less attractive or athletic, more emotionally unstable, and having lower self-esteem and academic ability. Ultimately, this profile is quite characteristic of the cyberbullying victim role, as revealed in past studies [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…On the other hand, the results suggest that adolescents who are not involved in cyberbullying, although not actively participating in these behaviors, may observe this on-line bullying of others, leading them to be concerned or distressed about the possibility of being criticized or made fun of themselves. Along these lines, some studies have identified problems of psycho-emotional adjustment in the cyberbullying observers [18,24,47] as well as a low self-concept and feelings of sadness, impotence, guilt, and fear. So, these negative emotional consequences may lead to a greater aversion and fear related to others who they do not know, for fear of becoming a victim [46].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, seven studies (eight mediation results) were included in the meta-analysis of the indirect effect of bullying on academic achievement through cognitive-motivational factors. There were an additional four studies [15,51,52,67] that did not test mediation nor provide data that allowed for the calculation of the indirect effect. However, because such studies looked at both the association between bullying and academic achievement and bullying and motivational factors, we decided to present their effect size findings in the meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%